Comparative company law - Gerner-Beuerle, Carsten; Schillig, Michael (Oxford Oxford University Press, 2019)
Comparative Company Law provides a systematic and coherent exposition of company law across jurisdictions, augmented by extracts taken from key judgments, legislation, and scholarly works. It provides an overview of the legal framework of company law in the US, the UK, Germany, and France, as well as the legislative measures adopted by the EU and the relevant case law of the Court of Justice. 0The comparative analysis of legal frameworks is firmly grounded in legal history and legal and economic theory and bolstered by numerous extracts (including extracts in translation) that offer the reader an invaluable insight into how the law operates in context. The book is an essential guide to how company law cuts across borders, and how different jurisdictions shape the corporate lifespan from its formation by way of incorporation to its demise (corporate insolvency) and eventual dissolution. In addition, it offers an introduction to the nature of the corporation, the framework of EU company law, incorporation and corporate representation, agency problems in the firm, rights of stakeholders and shareholders, neutrality and defensive measures in corporate control transactions, legal capital, piercing the corporate veil, and corporate insolvency and restructuring law.
Includes bibliographical references and index.
Keywords: Comparative law. -- Electronic books; Corporation law -- France; Corporation law -- Germany; Corporation law -- Great Britain; Corporation law -- United States